Biofilm Inhibition and Antibacterial Potential of Different Varieties of Garlic (Allium sativum) Against Sinusitis Isolates. Issue 4 (14th October 2021) - Shahid, Muhammad; Naureen, Ishrat; Riaz, Muhammad; Anjum, Fozia; Fatima, Hina; Rafiq, Muhammad Asif
Sinusitis or rhinosinusitis is inflammation of the paranasal sinuses which can be due to autoimmune, allergy, and infection problems. Current study was aimed to evaluate the antibiofilm and antibacterial potential of different varieties of A sativum . Four different varieties (China white, China pink, Desi white, and Desi pink) were used and extracted with methanol and water. Results of antioxidant analysis of A sativum extracts showed that all varieties of garlic have considerable quantity of flavonoids with significant DPPH inhibition and reductive potential. Antibacterial activity of A sativum extracts was tested against different Gram negative and Gram-positive sinusitis isolates. All the sinusitis isolates were susceptible to both methanolic and aqueous extracts of different varieties of A sativum with least MIC values. Antibiofilm potential of extracts against sinusitis isolates was evaluated through crystal violet assay, and all extracts of A sativum were significantly effective against destruction of microbial biofilm. In summary, A sativum extracts possess effective antibacterial and antibiofilm activity against sinusitis isolates and can be utilized for prevention of drug resistance against sinusitis infections and further evaluation is necessary.